Novel Modulators of Asthma and Allergy: Exosomes and MicroRNAs - Sastre, Beatriz; Cañas, José A.; Rodrigo-Muñoz, José M.; del Pozo, Victoria (Frontiers in Immunology, 2017)
Intercellular communication is crucial to the immune system response. In the recent years the discovery of exosomes has changed the way immune response orchestration was understood. Exosomes are able to operate as independent units that act as mediators in both physiological and pathological conditions. These structures contain proteins, lipidic mediators, and nucleic acids, and notoriously include microRNAs (miRNAs). miRNAs are short RNA sequences (around 19–22 nucleotides) with a high phylogenetic conservation and can partially or totally regulate multiple mRNAs, inhibiting protein synthesis. In respiratory diseases such as asthma and allergic sensitization, exosomes released by several cell types and their specific content perform crucial functions in the development and continuation of the pathogenic mechanisms. Released exosomes and miRNAs inside them have been found in different types of clinical samples, such as bronchoalveolar lavage fluids and sputum supernatants, providing new data about the environmental factors and mediators that participate in the inflammatory responses that lead to the exacerbation of asthma. In this review, we summarize our current knowledge of the role of exosomes and miRNAs in asthma and allergic sensitization, paying attention to the functions that both exosomes and miRNAs are described to perform through the literature. We review the effect of exosomes and miRNAs in cells implicated in asthma pathology and the genes and pathways that they modify in them, depicting how their behavior is altered in disease status. We also describe their possible repercussion in asthma diagnosis through their possible role as biomarkers. Therefore, both exosomes and miRNAs can be viewed as potential tools to be added to the arsenal of therapeutics to treat this disease.